Frailty as biographical disruption. Issue 4 (10th May 2021) - Cluley, Victoria; Martin, Graham; Radnor, Zoe; Banerjee, Jay
Abstract: Biographical disruption positions the onset of chronic illness as a major life disruption in which changes to body, self and resources occur ( Sociology of Health & Illness, 4, 1982, 167–182). The concept has been used widely in medical sociology. It has also been subject to critique and development by numerous scholars. In this paper, we build on recent developments of the concept, particularly those taking a phenomenological approach, to argue that it can also help in understanding other disruptive health‐related experiences across the life course, in this case the onset of frailty. We draw on the findings of 30 situated interviews with frail older people, relating their experiences of frailty to the concept of biographical disruption. We show that frailty shares many similarities with the experience of chronic illness. Using the lens of biographical disruption to understand frailty also offers insights relevant to recent debates around both concepts, and on the continued relevance of the idea of biographical disruption given changing experiences of health and illness, including the circumstances in which biographical disruption is more and less likely to be experienced. Finally, we reflect on the potentials and limitations of applying the concept to a health‐related condition that cannot be categorised as a disease.